Habitat Selection and Threats of Red Fox (Vulpes Vulpes) in Rara National Park, Nepal - Magar, Suresh Kumar Thapa; Dhamala, Man Kumar (Review of Environment and Earth Sciences, 2019)
Habitat selection is an important aspect of ecology to understand the relationship between the animals, its habitat and its resources. In an effort to understand the habitat selection by red fox and to explore its threats in relation to the people, the present study was conducted in Rara National Park, Nepal. Habitat variables were recorded in presence and absence plot (based on the signs of scat) along the elevation transect walk with associated topographic features (elevation, slope, aspect, distance to water, distance to a village) and vegetation features (tree species, shrub species, herb species and canopy cover). Using the Principal Component Analysis and Partial Least Square Regression model it was found that habitat variables such as distance to water, distance to village, major trees and major shrubs explained the presence and distribution of red fox in the study area. Data were collected from Key Informant Interview and schedule survey employing a convenience sampling method to know the cause of conflict and people’s perceptions towards red fox in the study area. Of the 35 respondents, 33 (94.2%) perceived that crop and livestock depredation was the major problem caused by the wild animals where most destructive wild animals were Sus scrofa (27.27%), Presbytis entellus (12.12%), Hystrix brachyura (15.15%) and Canis aureus (21.21%) followed by the red fox (12.12%). Threats ranking was conducted by questionnaire survey through purposive sampling method. Relative Importance Index (RII) technique was used to rank the threats.